ИНТЕРНЕТ КАК СПОСОБ СОЦИАЛЬНОЙ КОММУНИКАЦИИ - CухинаВ. Ф.; Шапаренко, Е. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
В статье исследованы особенности развития Интернета как способа осуществления всех видов социальной коммуникации. Осуществлен краткий анализ основных социальных функций Интернета, которые способны не только к позитивным, но и к негативным проявлениям. Предложено авторское определение компьютерной (информационной) социальной сети. Сделан акцент на влиянии Интернета на личностную сферу пользователей и на украинское общество. В. Ф. Сухіна, О. В. Шапаренко ІНТЕРНЕТ ЯК СПОСІБ СОЦІАЛЬНОЇ КОМУНІКАЦІЇ В статті досліджено особливості розвитку Інтернету як способу здійснення усіх можливих видів соціальної комунікації. Здійснено стислий аналіз основних соціальних функцій Інтернету здатних не тільки до позитивних, але й до негативних проявів. Запропоновано авторське визначення комп’ютерної (інформаційної) соціальної мережі. Зроблено акцент на впливі Інтернету на особистісну сферу користувачів та на українське суспільство. Ключові слова: Інтернет, соціальна комунікація, функції Інтернету, комп’ютерна (інформаційна) соціальна мережа, комп’ютероманія. V. Sukhina, Ye. Shaparenko INTERNET AS A MEANS OF SOCIAL COMMUNICATION The paper researches development peculiarities of the Internet as a means of all possible types of social communication and provides analysis of the main social functions of the Internet which may have both positive and negative effects. An author’s definition of computer (information) social network has been proposed. The emphasis was made on the impact of the Internet on the personal sphere of users and the Ukrainian society. Keywords: Internet, social communication, functions of the Internet, computer (information) social network, computermania.